CARGO SECURING DURING TRANSPORT ON THE RABA VEHICLE (Perner's Contacts, 2016)
The article deals with the evaluation of the transport experiment in Hungary using a Raba truck in order to show the deficiencies of the input data used for the purpose of cargo securing on vehicles. Statistical evaluation provides an overview of basic statistical characteristics, including the interpretation of significant values. The article contains model of loading, which illustrates the problem of using average – normatively set values of acceleration coefficients when determining the inertial forces acting during transport.
Keywords: cargo securing; inertial forces; transport; acceleration coefficients; statistical characteristics